2021
DOI: 10.1021/acs.biomac.1c00441
|View full text |Cite
|
Sign up to set email alerts
|

Associative Behavior of Lignosulphonates in Moderately Concentrated Water, Water–Salt, and Water–Alcoholic Media

Abstract: Industrial derivatives of lignin lignosulfonates are produced during sulfite delignification of wood. They are characterized by a wide molecular weight distribution, polyfunctionality, and lack of crystallinity. The presence of hydrophobic and hydrophilic domains in the lignosulfonate macromolecular system determines the amphiphilic and polyelectrolyte properties of this biopolymer. As a polyelectrolyte, lignosulfonates (LSs) show complex conformational and phase behavior, which can be controlled by a wide ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…Many of the above data were confirmed and supplemented by us in our work . Using various physicochemical methods (conductometry, viscometry, potentiometry, photometry, and tensiometry), the aggregation of a number of LS was studied.…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Many of the above data were confirmed and supplemented by us in our work . Using various physicochemical methods (conductometry, viscometry, potentiometry, photometry, and tensiometry), the aggregation of a number of LS was studied.…”
Section: Introductionsupporting
confidence: 63%
“…Many of the above data were confirmed and supplemented by us in our work. 34 Using various physicochemical methods (conductometry, viscometry, potentiometry, photometry, and tensiometry), the aggregation of a number of LS was studied. It has been shown that an increase in molecular weight, LS concentration, temperature, the presence of an indifferent electrolyte (KCl), and ethyl alcohol lead to a change in the intensity of electrostatic, hydrophobic, and van der Waals interactions and hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular weight distribution of SL is wide, ,, so coarse-grained models of SL with different molecular weights (Table S1) had also gained attention in the work. Therefore, the effect of molecular weight of SL on the SL aggregates in ethanol was also investigated by DPD simulations.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, a typical STEM image from experimental methods (Figure S1) showed that the independent SL molecules really led to SL aggregates with various micro sizes and irregular structures (Figure f). Various SLs indeed have complex conformations . Moreover, based on the DPD results, it was considered that the occurrence of SL aggregates with various sizes was related to the various molecular weights of SL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation